Perspective Chapter: Academia as a Culture - The ‘Academy’ for Women Academics - Phillips, Matty (IntechOpen, 2022)
This review explores what is known about women’s experiences and identities within Australian public higher education to assist readers in contextualising the issue. In doing this, the chapter summarises what is known thus far about the key tensions that are experienced by women in academia, underpinned by the influence of the gender binary, heteronormativity, and intersectionality. Then, what is known about the academic identity thus far within the extant literature base is presented, as well as how the identity formation process can be complex and difficult to engage in for women academics. To conclude the chapter, the tensions are extended on to explore how academic ways of being were introduced and influenced by coloniality, as well as acknowledging how the neoliberal episteme has become embedded within the academic system to influence women and their academic experience over time. The aim of this chapter is to liberate thinking surrounding the experiences of women academics through the reviewing and discussion of the literature base and encourage further conversations and connections between academics worldwide surrounding this topic.